Learning YARN : moving beyond MapReduce--learn resource management and big data processing using YARN - Arora, Akhil; Mehrotra, Shrey (Community experience distilled., 2015)
Moving beyond MapReduce - learn resource management and big data processing using YARN About This Book Deep dive into YARN components, schedulers, life cycle management and security architecture Create your own Hadoop-YARN applications and integrate big data technologies with YARN Step-by-step guide to provision, manage, and monitor Hadoop-YARN clusters with ease Who This Book Is For This book is intended for those who want to understand what YARN is and how to efficiently use it for the resource management of large clusters. For cluster administrators, this book gives a detailed explanation of provisioning and managing YARN clusters. If you are a Java developer or an open source contributor, this book will help you to drill down the YARN architecture, write your own YARN applications and understand the application execution phases. This book will also help big data engineers explore YARN integration with real-time analytics technologies such as Spark and Storm. What You Will Learn Explore YARN features and offerings Manage big data clusters efficiently using the YARN framework Create single as well as multi-node Hadoop-YARN clusters on Linux machines Understand YARN components and their administration Gain insights into application execution flow over a YARN cluster Write your own distributed application and execute it over YARN cluster Work with schedulers and queues for efficient scheduling of applications Integrate big data projects like Spark and Storm with YARN In Detail Today enterprises generate huge volumes of data. In order to provide effective services and to make smarter and more intelligent decisions from these huge volumes of data, enterprises use big-data analytics. In recent years, Hadoop has been used for massive data storage and efficient distributed processing of data. The Yet Another Resource Negotiator (YARN) framework solves the design problems related to resource management faced by the Hadoop 1.x framework by providing a more scalable, efficient, flexible, and highly available resource management framework for distributed data processing. This book starts with an overview of the YARN features and explains how YARN provides a business solution for growing big data needs. You will learn to provision and manage single, as well as multi-node, Hadoop-YARN clusters in the easiest way. You will walk through the YARN administration, life cycle management, application execution, REST APIs, schedulers, security framework and so o...